THE USE OF PROVERBS AND SAYINGS IN THE STORIES OF ABDULLAH KAHHAR - Sharipova Nilufar Shaxrillo qizi; Fayzullayeva Shahnoza Husen qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The article will examine, using the example of Abdullah Kahhor's works, various aspects of proverbs and sayings that are examples of folk art, the goals and objectives of their use in works of art, their significance for understanding the work and how they are transmitted to the reader.